In Vitro Micropropagation of Aquarium Plants Pearl Grass Hemianthus micranthemoides (Nuttall) and Micro Sword Grass Lilaeopsis brasiliensis (Glaziou) Affolter (Apiaceae) - Ing, Nguang Siew; Chew, Ha Hou; Nor Hasima, Mahmod; Rokiah, Zainuddin; Tajul Afif, Abdullah (2019)
Hemianthus micranthemoides and Lileaopsis brasiliensis are nowadays sold in the form of tissue culture production by aquaria and ornamental trade in Malaysia. However, there is no to limited report about in vitro micropropagation of both aquarium plants. In this study, an experimental procedure for micropropagation of both plants was documented. The propagation were done in Murashige and Skoog (MS) medium with eight combination of different concentration of 6-Benzylaminopurine with Naphteneacetic acid (BAP-NAA) and 1-phenyl-3-1,2,3- thiadizol-5-yl urea with Naphteneacetic acid (TDZ-NAA) following the rooting technique for 42 days. All treatments for 1 L MS medium were regulated to pH 5.7 to 5.8 and added with sucrose (30 g/L) and phytagel (2.5 g/L). All combination treatments had induced rooting. There was a significance different in the shoot regeneration of H. micranthemoides in all treatment (95% confidence level, F = 13.907, n = 240, p = 0.000), on the contrary there was no different were observed in shoot regeneration of L. brasiliensis treatment. Overall, all treatment of TDZNAA were significantly higher in the shoot regeneration than those in BAP-NAA treatment. Particularly the T7 (TDZ-NAA, 0.075: 0.1 mg/L) given highest result in diameter (1.626±0.213 cm) and area (1.724±0.308 cm2) of shoot clumps in H. micranthemoides, and formation of shoots (51.5±4.95), nodes (20.0±2.83) and roots (45.5±13.4) in L. brasiliensis. Hardening of in vitro cultured plantlets was done in aquatic laboratory. All of the plants survived and transferred into aquarium. This study has provided beneficial information in further micropropagation protocol for the mass production of both aquarium plants.